Compatibility Test of the Biculture Consortium of Thermophilic Bacteria from Mudiak Sapan Hot - Fahra Fahra; Irdawati Irdawati (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Thermophilic bacteria are bacteria that are resistant to hot temperatures and have several other advantages in producing industrial fields. Bacteria also exist in the form of a mixture (consortium) where the bacteria work together to produce enzymes. This study aims to examine the compatibility of thermophilic bacterial isolates. This research is descriptive in nature using the Spread Plate Method. The results showed that the thermophilic bacterial isolates tested (MS 9, MS 12, MS 18 and MS 17) and all their compatible partners were seen with no inhibition zones. Keywords : Biofuel, thermophilic bacteria, compatibility test.